Adubação nitrogenada e idade de corte na produção de matéria seca do capim-elefante no Cerrado - Flores, Rilner A.; Urquiaga, Segundo S.; Alves, Bruno J. R.; Collier, Leonardo S.; Morais, Rafael F. De; Prado, Renato De M. [UNESP] (Departamento de Engenharia Agrícola - UFCG, 2012)
The objective of this study was to investigate the effect of the application of N fertilizer and the cutting age on the dry biomass production of elephant grass. The experiment was performed with the variety Paraíso and planted in a Ferralsol in 2008 in the district of Gurupi (State of Tocantins). Four different rates of urea application were tested (0, 50, 100 and 150 kg ha-1) and harvests were made at 120, 150 or 180 days after germination (DAG) of the setts. The dry matter and total N accumulation were evaluated. Dry matter production increased with dose of N, the greatest effect being observed at 180 DAG. There was a linear increase in dry matter (R² = 0.75**) and N accumulation (R² = 0.96**) permitting a productivity of 34 t ha-1 of dry matter and an accumulation of 471 kg N ha-1. The N utilization efficiency (biomass production per unit of applied N) increased with plant age. The higher efficiency of N use favored the quality of biomass production for energy production owing to the higher fibre content.

Propôs-se, com este trabalho, avaliar o efeito da aplicação de N e da idade de corte na produção de biomassa e acúmulo de nitrogênio pelo capim-elefante. O experimento foi realizado com o capim-elefante cv. Paraíso, cultivado em um Latossolo Vermelho-Amarelo distrófico, município de Gurupi, TO, safra 2008/2009. Foram testadas quatro doses de N-uréia (0, 50, 100 e 150 kg ha-1) e três idades de corte do capim (120, 150 e 180 dias após o brotamento). Avaliou-se, em cada idade de corte, a produção de matéria seca da parte aérea (folhas e colmos) e o acúmulo de N na planta. A produção de matéria seca do capim-elefante aumentou com a adição de N porém o efeito foi maior para as plantas cortadas com 180 dias de idade. Encontrou-se um incremento linear na acumulação de matéria seca (R² = 0,75**) e na acumulação de N (R² = 0,96**), permitindo uma produtividade de 34 t ha-1 de matéria seca, que implicou em uma extração de N de 471 kg ha-1. A eficiência de utilização do N pela cultura variou com o aumento da idade da planta, o que significou maior quantidade de biomassa por unidade de N absorvido. O índice de eficiência mostra que o corte tardio pode favorecer a qualidade da biomassa para fins energéticos, por se tratar de um material mais fibroso.
Effect of nitrogen fertilizer and cutting age on the dry matter production of elephant grass in Savana
Keywords: Pennisetum purpureum; biomass; bioenergy; Pennisetum purpureum; biomassa; bioenergia